Remote fieldwork supervision for BCBA trainees - Britton, Lisa N.; Cicoria, Matthew J. (Academic Press, 2019)
Remote Fieldwork Supervision for BCBA Trainees prepares BCBAs for supervising certification candidates, providing structure, scope, and sequence for supervision, as well as tactical recommendations for providing independent fieldwork supervision in a distance context. The book helps to resolve common challenges in supervision arrangements, such as maintaining professional behavior and encouraging practitioner self-care. The book follows the Behavior Analyst Certification Board's Fifth Edition Task List, and then goes beyond the required 8-hour supervision training to teach important clinical skills, such as ACT, RFT, executive function skills, OBM, and curriculum-based measures.